Bridging Identities: The Political Participation of Chinese Indonesians in a Multicultural Landscape - Jeremi Kristo Malau; Maurisius Taufik Sabrias; Ignasius Ryan Febrinanda; Padre Pio; Fuzy Firda Zhan (CV. Era Digital Nusantara, 2026)
Abstract: The Chinese community has often received insufficient attention, despite historical evidence demonstrating their significant role in various fields, including religion, literature, language, art, and sports. Common representations of the Chinese ethnic group tend to be negative, portrayed as economically dominant but opportunistic, lacking political loyalty, lacking nationalism, and prioritizing self-interest. Historical accounts typically highlight their role in the economy, either as major traders or as controllers of trade routes deemed detrimental to the local population. Purpose: This article examines the shifting political identity and participation of Chinese Indonesians in the post-Reformasi era, a period marked by democratic opening and greater recognition of cultural diversity. The purpose of this study is to analyze how the political identity of Chinese Indonesians has transformed since the fall of the New Order and to explore its relationship with the broader development of multiculturalism in Indonesia. Design/Methodology/Approach: The methodology used was descriptive research with a qualitative approach. Data were collected through document study and literature review. Data analysis was conducted using content analysis, which analyzes text or documents and then narrative analysis to examine the collected narratives. Findings: The findings reveal a significant transformation in the political behavior of Chinese Indonesians from a historically passive stance shaped by discrimination, stigma, and restrictive state policies, they have increasingly become active participants in political processes. The study finds that government policies after 1998 which gradually restored cultural rights and citizenship equality played a crucial role in enabling this political reorientation. This change shows how greater institutional openness strengthens minority political agency. Originality/value: This research draws on its integrative analysis, linking political participation to identity reconstruction and multicultural practices as authenticity. As a value, this research offers a nuanced understanding of how minority groups reposition themselves within Indonesia's evolving democratic landscape.